A Cell‐Permeable Ester Derivative of the JmjC Histone Demethylase Inhibitor IOX1. Issue 3 (6th February 2014) - Schiller, Rachel; Scozzafava, Giuseppe; Tumber, Anthony; Wickens, James R.; Bush, Jacob T.; Rai, Ganesha; Lejeune, Clarisse; Choi, Hwanho; Yeh, Tzu‐Lan; Chan, Mun Chiang; Mott, Bryan T.; McCullagh, James S. O.; et al.
Abstract The 2‐oxoglutarate (2OG)‐dependent Jumonji C domain (JmjC) family is the largest family of histone lysine demethylases. There is interest in developing small‐molecule probes that modulate JmjC activity to investigate their biological roles. 5‐Carboxy‐8‐hydroxyquinoline (IOX1) is the most potent broad‐spectrum inhibitor of 2OG oxygenases, including the JmjC demethylases, reported to date; however, it suffers from low cell permeability. Here, we describe structure–activity relationship studies leading to the discovery of an n‐octyl ester form of IOX1 with improved cellular potency (EC50 value of 100 to 4 μM). These findings are supported by in vitro inhibition and selectivity studies, docking studies, activity versus toxicity analysis in cell cultures, and intracellular uptake measurements. The n‐octyl ester was found to have improved cell permeability; it was found to inhibit some JmjC demethylases in its intact ester form and to be more selective than IOX1. The n‐octyl ester of IOX1 should find utility as a starting point for the development of JmjC inhibitors and as a use as a cell‐permeable tool compound for studies investigating the roles of 2OG oxygenases in epigenetic regulation.